Individual Differences and Hemispheric Asymmetries for Language and Spatial Attention - O’Regan, Louise; Serrien, Deborah J. (Frontiers in Human Neuroscience, 2018)
Language and spatial processing are cognitive functions that are asymmetrically distributed across both cerebral hemispheres. In the present study, we compare left- and right-handers on word comprehension using a divided visual field paradigm and spatial attention using a landmark task. We investigate hemispheric asymmetries by assessing the participants’ behavioural metrics; response accuracy, reaction time and their laterality index. The data showed that right-handers benefitted more from left-hemispheric lateralisation for language comprehension and right-hemispheric lateralisation for spatial attention than left-handers. Furthermore, left-handers demonstrated a more variable distribution across both hemispheres, supporting a less focal profile of functional brain organisation. Taken together, the results underline that handedness distinctively modulates hemispheric processing and behavioural performance during verbal and nonverbal tasks. In particular, typical lateralisation is most prevalent for right-handers whereas atypical lateralisation is more evident for left-handers. These insights contribute to the understanding of individual variation of brain asymmetries and the mechanisms related to changes in cerebral dominance.